2013
DOI: 10.1002/eji.201343532
|View full text |Cite
|
Sign up to set email alerts
|

Extrathymic induction of Foxp3+ regulatory T cells declines with age in a T‐cell intrinsic manner

Abstract: Extrathymically induced Foxp3+ regulatory T (Treg) cells contribute to the pool of Treg cells and are implicated in the maintenance of immune tolerance at environmental interfaces. The impact of T-cell senescence on their generation and function is, however, poorly characterized. We report here that steady-state induction of Foxp3 is impaired in aged T cells in vivo. In vitro assays further revealed that this defective generation of Treg cells was independent from the strength of TCR stimulation and arose befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 30 publications
(43 reference statements)
1
27
0
Order By: Relevance
“…Our results shed light on a fundamental part of Treg-cell homeostasis, which is the extrathymic generation of Treg cells. A basal level of conversion takes place in steady state, which is in accordance with the hypothesis that peripheral homeostasis depends on presentation of self, food, and flora-derived antigens under tolerogenic conditions, leading to conversion of Tnaive cells into pTreg cells [18,52,53]. Here we observed again an essential difference between LNs and spleen.…”
Section: Discussionsupporting
confidence: 91%
“…Our results shed light on a fundamental part of Treg-cell homeostasis, which is the extrathymic generation of Treg cells. A basal level of conversion takes place in steady state, which is in accordance with the hypothesis that peripheral homeostasis depends on presentation of self, food, and flora-derived antigens under tolerogenic conditions, leading to conversion of Tnaive cells into pTreg cells [18,52,53]. Here we observed again an essential difference between LNs and spleen.…”
Section: Discussionsupporting
confidence: 91%
“…Peripheral Treg induction therefore presumably decreases in parallel to thymic involution and Tconv production. However, Carpentier et al [26] have shown that differentiation of naïve Tconv from old mice into Treg is less efficient both in vitro and in vivo. The defective production of pTreg in the elderly may be due to a T-cell-intrinsic factor [26] .…”
Section: Aging and Treg Productionmentioning
confidence: 99%
“…However, Carpentier et al [26] have shown that differentiation of naïve Tconv from old mice into Treg is less efficient both in vitro and in vivo. The defective production of pTreg in the elderly may be due to a T-cell-intrinsic factor [26] . It appears therefore that the peripheral differentiation of pTreg drops with age because of a combination of reduced thymic output and potentially thymocyte-intrinsic factors.…”
Section: Aging and Treg Productionmentioning
confidence: 99%
“…Furthermore, myocardial senescence is associated with cardiomyocyte cell death, leading to increased exposure of heartspecific antigens to immune cells (26). From the immunological perspective, aging is accompanied by an increased systemic inflammatory basal tone (27)(28)(29) and with defective maintenance of immunological tolerance (30)(31)(32).…”
mentioning
confidence: 99%